2021
DOI: 10.1111/evo.14329
|View full text |Cite
|
Sign up to set email alerts
|

Softness of selection and mating system interact to shape trait evolution under sexual conflict

Abstract: Sexual selection and sexual conflict play central roles in driving the evolution of male and female traits. Experimental evolution provides a powerful approach to study the operation of these forces under controlled environmental and demographic conditions, thereby allowing direct comparisons of evolutionary trajectories under different treatments such as mating systems. Despite the rapid progress of experimental and statistical techniques that support experimental evolution studies, we still lack clear theore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…A possibility is that the behavioral divergence that we have exposed responds to the differential softness of selection between the structured (where soft selection applies) and nonstructured (where hard selection operates) populations (see Fig. 1, Methods, Supporting Information;Wallace 1975;Saccheri and Hanski 2006;Débarre and Gandon 2011;Reznick 2016;Bell et al 2021;Li Richter and Hollis 2021). If this was the case, soft selection in structured populations would have allowed the evolution of plasticity in male behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A possibility is that the behavioral divergence that we have exposed responds to the differential softness of selection between the structured (where soft selection applies) and nonstructured (where hard selection operates) populations (see Fig. 1, Methods, Supporting Information;Wallace 1975;Saccheri and Hanski 2006;Débarre and Gandon 2011;Reznick 2016;Bell et al 2021;Li Richter and Hollis 2021). If this was the case, soft selection in structured populations would have allowed the evolution of plasticity in male behavior.…”
Section: Discussionmentioning
confidence: 99%
“…1, Methods , Supporting Information; Wallace 1975; Saccheri and Hanski 2006; Débarre and Gandon 2011; Reznick 2016; Bell et al. 2021; Li Richter and Hollis 2021). If this was the case, soft selection in structured populations would have allowed the evolution of plasticity in male behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In anisogamous species, however, females tend to be demographically dominant [ 50 ], meaning that their performance is a stronger determinant of population growth than the number, or fitness, of males. One way to phrase this is that selection is softer on males than on females [ 51 ], and it is well known that soft selection can maintain population fitness at demographically adequate levels even if a straightforward computation of mutational load would predict dismal performance [ 52 , 53 ]. Classic theory on load and soft selection, however, does not differentiate between males and females, and because reproduction often involves direct behavioural contact between contestants or potential mates, very diverse outcomes are possible.…”
Section: It Is Not All About Food: Individual Success At the Expense Of Conspecificsmentioning
confidence: 99%
“…Male-biased genes in many species tend to exhibit higher rates of evolution at both the coding sequence and the expression level (Ranz et al 2003; Khaitovich et al 2005; Sharma et al 2014; Lipinska et al 2015; Whittle and Extavour 2019; Lichilin et al 2021). While early work in Drosophila melanogaster has interpreted this as the result of stronger sexual selection acting in males (Proschel et al 2006; Sawyer et al 2007), studies in other species have found that such accelerated patterns of evolution are instead more consistent with relaxed constraint (Gershoni and Pietrokovski et al 2014; Harrison et al 2015; Sayadi et al 2019; Dapper and Wade, 2020; Djordjevic et al 2021), and experimental evolution results were somewhat mixed (Hollis et al 2014; Veltsos et al 2017; Li Richter and Hollis 2021).…”
Section: Introductionmentioning
confidence: 99%